PENDAMPINGAN BELAJAR TKA (TES KOMPETENSI AKADEMIK) MATEMATIKA SISWA KELAS VI DI LINGKUNGAN GEREJA SHALLOM WAMENA - Mindo H. Sinambela; Citra R. Napitupulu; Christine M. Rumpaisum; Sutarman Borean; Barthon Wenda; Andinus Yanengga (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The Academic Competency Test (TKA), established under Permendikdasmen Number 9 of 2025, positions academic achievement as one of the key indicators for student admission to the next level of education. The implementation of TKA in mathematics presents considerable challenges due to the reasoning-based and Higher Order Thinking Skills (HOTS) demands of its questions, causing many students to experience difficulties and anxiety. This community service activity aimed to enhance the academic readiness of sixth-grade students in facing the Mathematics TKA through a coaching-based learning assistance program. The activity was conducted over eight days (March 16–24, 2026) at the Shallom Sunday School Building in Wamena, involving 9 participants aged 11–12 years from several primary schools in the Wamena area. The method encompassed three stages: preparation, implementation, and evaluation. Academic readiness was measured through 40 evaluation items aligned with the TKA framework within a 120-minute session, supported by observational assessment throughout the program. Results demonstrated improved conceptual understanding in number operations, measurement, and two- and three-dimensional geometry. Participants also grew more familiar with reasoning-based question types and exhibited increased motivation and confidence. The program received full support from the church and parents as implementation partners, confirming that coaching-based TKA preparation effectively enhances academic readiness while strengthening collaboration between higher education institutions and the community. ABSTRAK Tes Kemampuan Akademik (TKA) berdasarkan Permendikdasmen Nomor 9 Tahun 2025 menjadikan capaian akademik sebagai salah satu indikator penerimaan peserta didik ke jenjang pendidikan berikutnya. Pelaksanaan TKA pada mata pelajaran matematika menghadapi tantangan signifikan karena karakteristik soal yang menuntut kemampuan penalaran dan Higher Order Thinking Skills (HOTS), sehingga banyak siswa mengalami kesulitan dan kecemasan. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kesiapan akademik siswa kelas VI dalam menghadapi TKA Matematika melalui program pendampingan belajar berbasis coaching. Kegiatan dilaksanakan selama delapan hari (16–24 Maret 2026) di Gedung Sekolah Minggu Shallom Wamena, melibatkan 9 peserta berusia 11–12 tahun dari beberapa sekolah dasar di wilayah Wamena. Metode yang digunakan mencakup tiga tahap: persiapan, pelaksanaan, dan evaluasi. Kesiapan akademik diukur melalui 40 butir soal evaluasi sesuai kisi-kisi TKA dengan alokasi waktu 120 menit, serta didukung pengamatan selama proses pendampingan. Hasil kegiatan menunjukkan peningkatan pemahaman konsep matematika pada materi operasi bilangan, pengukuran, serta geometri bangun datar dan ruang. Peserta juga semakin familiar dengan tipe soal berbasis penalaran serta menunjukkan peningkatan motivasi dan kepercayaan diri. Program ini mendapat dukungan penuh dari pihak gereja dan orang tua, membuktikan bahwa pendampingan berbasis coaching efektif meningkatkan kesiapan akademik sekaligus memperkuat sinergi antara perguruan tinggi dan komunitas.